Hydraulic characterization of a stabilized residual soil with brick dust and lime waste [Caracterización hidráulica de un suelo residual estabilizado con polvo de ladrillo y residuos de cal] (2016)
The use of industrial residues as construction materials is presented as an interesting functional, economic and environmental alternative for improving low traffic roads, and in particular, waste from the construction industry with high brick dust content. This paper presents the hydraulic properties in unsaturated conditions obtained for a sandy soil stabilized with brick dust, activated with lime residues. the characteristic curves were determined considering the effect of moisture curing or drying and wetting path. The curves obtained experimentally were adjusted with the models proposed by Van Genuchten, Fredlund & Xing and Brooks & Corey. Additionally permeability tests were performed with varying head. The results indicate that the addition of the stabilizer increases the saturation moisture in the soil, causing a decrease in the pores of the sample allowing greater water retention. © 2016 International Society for Rock Mechanics. All rights reserved.